Clinical outcome and laboratory markers for predicting disease activity in patients with disseminated opportunistic infections associated with anti-interferon-γ autoantibodies - Nasikarn Angkasekwinai (2020)
© 2019 Angkasekwinai et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background Clinical courses and treatment outcomes are largely unknown in patients with adult-onset immunodeficiency associated with anti-interferon-gamma autoantibodies due to the fact that it was recently recognized and anti-IFN-γ auto-Abs detection is not widely available. Methods and findings Non-HIV-infected adult patients with detectable anti-IFN-γ auto-Abs diagnosed and followed at Siriraj Hospital, Bangkok, Thailand during January 2013 to November 2016 were prospectively studied. At each follow-up visit, patients were classified as stable or active disease according to symptoms and signs, and all proven OIs were recorded. Laboratory parameters, including erythrocyte sedimentation rate, C-reactive protein, and anti-IFN-γ auto-Abs level, were compared between active and stable disease episodes. We identified 80 patients with this clinical syndrome and followed them up during study period. Seventy-nine patients developed overall 194 proven opportunistic infections. Mycobacterium abscessus (34.5%) and Salmonella spp. (23.2%) were the two most common pathogens identified among these patients. Sixty-three patients were followed for a median of 2.7 years (range 0.6–4.8 years). Eleven (17.5%) patients achieved the drug-free remission period for at least 9 months. Four patients died. Anti-IFN-γ auto-Abs concentration was significantly lower at baseline and decreased over time in the drug-free remission group compared to another group (p = 0.001). C-reactive protein, erythrocyte sedimentation rate and white cell count were found to be useful biomarkers for determining disease activity during follow-up. Conclusions Reinfection or relapse of OIs is common despite long-term antimicrobial treatment in patients with anti-IFN-γ auto-Abs. Treatment to modify anti-IFN-γ auto-Abs production may improve long-term outcomes in this patient population.